A porous-based discontinuous model for ductile fracture in metals - Said Schicchi, Diego (2015)
A discontinuous model aimed at modeling ductile fracture for metals is presented. The effect of microvoid nucleation, growth and coalescence on the inelastic response of structural metals is modeled through a suitable interface proposal for cracking analysis. The discontinuos proposal is completely conceived within the general framework of fracture mechanics and porous plasticity concepts. The porosity affects the strength parameters and softening rules defining the failure initiation and post-cracking response of the interface. To demonstrate the soundness and capability of the proposed formulation, a comparative study against numerical simulations obtainable from a classical well-known continuous approach for capturing ductile fracture, based on finite element analysis, is presented.